0
$\begingroup$

Find the angle between two tangents from an external point $(x_1,y_1)$ to the circle $x^2+y^2=a^2$ .

Below is my attempt at the problem:

$x^2+y^2=a^2$,Differentiating we get $\dfrac{dy}{dx}=\dfrac{-x}{y}.$

Hence slope will be $\dfrac{-a_1}{b_1}$ at the point $(a_1,b_1)$ for the first tangent.

Similarly slope will be $\dfrac{-a_2}{b_2}$ at the point $(a_2,b_2)$ for the second tangent.

Now $a_1^2+b_1^2=a^2,a_2^2+b_2^2=a^2\implies (a_2-a_1)(a_2+a_1)+(b_2-b_1)(b_2+b_1)=0$

$\dfrac{-a_1}{b_1}=\dfrac{y_1-b_1}{x_1-a_1}\implies a_1x_1+y_1b_1=a_1^2+b_1^2$

Similarly $a_2x_2+y_2b_2=a_2^2+b_2^2$

Now to find the angle between them we have to evaluate $\tan\alpha=\dfrac{a_1b_2-a_2b_1}{b_1b_2+a_1a_2}$

How to eliminate $a_1,b_1,a_2,b_2$? from here? Please help.

$\endgroup$
  • $\begingroup$ But this angle is not unique...it's okay to depend on the contact points $\endgroup$ – Martín Vacas Vignolo Dec 29 '17 at 14:15
2
$\begingroup$

For $a>0$ it's just $$2\arcsin\frac{a}{\sqrt{x_1^2+y_1^2}}.$$

Indeed, let $A(x_1,y_1)$, $O(0,0)$ and $B$ be one of touching points.

Thus, the needed angle it's $2\measuredangle OAB$, $OA=\sqrt{x_1^2+y_1^2}$, $OB=a$ and $\measuredangle ABO=90^{\circ}$.

$\endgroup$
  • $\begingroup$ How did you get that? Will you please explain $\endgroup$ – Learnmore Dec 29 '17 at 14:17
  • $\begingroup$ $$O(0,0);P(x_1,y_1);|OP|=?$$ $\endgroup$ – lab bhattacharjee Dec 29 '17 at 14:18
  • $\begingroup$ @New_User I added something. See now. $\endgroup$ – Michael Rozenberg Dec 29 '17 at 14:26
  • $\begingroup$ Yes it is clear now for me Thank you $\endgroup$ – Learnmore Dec 29 '17 at 14:28
  • $\begingroup$ You are welcome! $\endgroup$ – Michael Rozenberg Dec 29 '17 at 14:30
1
$\begingroup$

Using The line $y=mx+c$ is a tangent to $x^2+y^2=a^2$ if:,

the equation any tangent to $x^2+y^2=a^2$ is $$y=mx\pm a\sqrt{m^2+1}$$

$$\iff(y-mx)^2=a^2(m^2+1)\iff m^2(a^2-x^2)+2mxy+a^2-y^2=0$$

Now this pair of tangents pass through $(x_1,y_1)$

$$m^2(a^2-x_1^2)+2mx_1y_1+a^2-y_1^2=0$$ whose roots are $m_1,m_2$

$$\implies m_1+m_2=\dfrac{-2x_1y_1}{a^2-x_1^2}$$ $$m_1m_2=\dfrac{a^2-y_1^2}{a^2-x_1^2}$$

We need to find $$\dfrac{|m_2-m_1|}{1+m_1m_2}=\dfrac{\sqrt{(m_2+m_1)^2-4m_1m_2}}{1+m_1m_2}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.